Plant parasitic nematodes associated with wheat in the state of Rio Grande do Sul, Brazil - Luz, Wilmar Cório da (Pesquisa Agropecuaria Brasileira, 2014)
Forteen genera of plant parasitic nematodes were detected from soil and roots collected from wheat (Triticum aestivum L.) fields in Rio Grande do Sul State: Aphelenchus, Aphelenchoides, Criconemoides, Ditylenchus, Hoplolaimus, Longidorus, Meloidogyne, Paratylenchus, Pratylenchus, Radopholus, Trichodorus, Tylenchus, Tylenchorrhynchus e Xiphinema. The species identified were: Aphelenchus avenae (Bastian 1865). Ditylenchus dipsasi (Kühn 1857. Filipjev 1936), Hoplolaimus tylenchiformis ( Daday 1905), Meloidogyne acrita (Esser, Perry & Taylor 1976), Pratylenchus minyus (Sher & Alien 1953) e Tylenchorrhynchus striatus (Alien 1955). All species reported except Aphelenchus avenae were first reported in wheat association in Brazil.